The Impact of the Level and Timing of Parental Resources on Child Development and Intergenerational Mobility - Sadegh S. M. Eshaghnia; James J. Heckman; Rasmus Landerso (Institute of Labor Economics (IZA), 2024)
This study explores relationships between parental resource trajectories and child development, and their implications for intergenerational mobility. By modifying the child skill formation technology to incorporate new skills during adolescence, we analyze the importance of the timing of family resources on life outcomes, educational attainment and participation in crime. Parental financial resources partially offset deficiencies in nonpecuniary inputs to children's human capital. Estimates of the intergenerational influence on child outcomes are strongly influenced by the choice of lifetime versus snapshot parental income measures. The most predictive ages of children when family resources are measured vary by the outcome analyzed.
Keywords: I24; D31; I30; 330; intergenerational elasticity; lifecycle measures; child development; compensating for family disadvantage